2018
DOI: 10.2134/agronj2017.12.0703
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Management of Photosystem II‐ and HPPD‐inhibitor‐Resistant Palmer amaranth in Corn

Abstract: P almer amaranth (Amaranthus palmeri S. Wats.) is the most problematic and difficult to control weed among crops in the United States (Chahal et al., 2015, 2017; Kohrt and Sprague, 2017). Palmer amaranth biotypes resistant to microtubule-, acetolactate synthase (ALS)-, photosystem (PS) II-, 5-enol-pyruvylshikimate-3-phosphate synthase (EPSPS)-, hydroxyphenylpyruvate dioxygenase (HPPD)-, and protoporphyrinogen oxidase (PPO)-inhibitor herbicides have been reported in the United States (Heap, 2017a). Photosystem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
(39 reference statements)
1
12
0
Order By: Relevance
“…Residual herbicides used in this study were a premix of two to four herbicide active ingredients and were selected for their efficacy for controlling atrazine-and HPPD inhibitor-resistant Palmer amaranth. Chahal and Jhala (2018) Palmer amaranth biotypes that are resistant to multiple herbicide sites of action are difficult to control with the use of single herbicides in corn-soybean cropping systems and requires an IWM program. Information about emergence pattern of Palmer amaranth affected by management strategies such as tillage timings or residual herbicide could help growers plan an IWM program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual herbicides used in this study were a premix of two to four herbicide active ingredients and were selected for their efficacy for controlling atrazine-and HPPD inhibitor-resistant Palmer amaranth. Chahal and Jhala (2018) Palmer amaranth biotypes that are resistant to multiple herbicide sites of action are difficult to control with the use of single herbicides in corn-soybean cropping systems and requires an IWM program. Information about emergence pattern of Palmer amaranth affected by management strategies such as tillage timings or residual herbicide could help growers plan an IWM program.…”
Section: Resultsmentioning
confidence: 99%
“…Herbicides applied PRE at crop planting generally lose their residual activity 14 to 35 d after application depending on soil type, application rate of herbicide, weather conditions, and weed species present in the field (Jhala et al 2015;Wiggins et al 2015). Chahal and Jhala (2018) reported that atrazine/mesotrione/S-metolachlor, atrazine/fluthiacet/pyroxasulfone, acetochlor/clopyralid/flumetsulam, and saflufenacil/dimethenamid applied PRE provided 88% to 97% control of atrazine and HPPD-inhibitor (mesotrione, tembotrione, or topramezone)-resistant Palmer amaranth; however, an additional POST herbicide was needed for control of late-emerging Palmer amaranth cohorts. Recent studies have reported that PRE herbicides can delay the critical period of weed removal in corn and soybean compared with no-residual herbicide due to reduced early-season weed emergence (Knezevic et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It is ideal to have horseweed plants shorted than 15 cm at the time of POST herbicide application to achieve effective control in soybean. Horseweed biotypes resistant to cloransulam have been reported in the United States and Canada (Byker et al 2013b;Trainer et al 2005), and even though tillage or herbicide applied in fall or spring followed by a PRE or a POST herbicide provided similar control as when followed by a PRE and POST herbicide, a PRE herbicide should be included to reduce later-season horseweed emergence and should include an herbicide with an additional effective site of action in the program for herbicide-resistant weed management (Chahal and Jhala 2018;Ganie and Jhala 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Management of GR Palmer amaranth in no-till corn and soybean production systems is primarily dependent on sequential herbicide programs of residual herbicides applied at planting, followed by a POST herbicide when plants are less than 15 cm tall (Chahal et al 2017;Chahal and Jhala 2018;. Most weed management decisions are based on potential yield loss compared to the cost of weed management; however, weed escapes from POST herbicide and late-season weed emergence are usually ignored once normal yield has been achieved (Bagavathiannan and Norsworthy 2012).…”
Section: Introductionmentioning
confidence: 99%